(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article analyzes whether drama teaching has strained the dominant power relations and their regulatory regimes in the 54 didactic works approved in the National Book and Didactic Material Program of 2021 for the New High School, in the area of Languages and their Technologies. We sought to analyze, from the perspective of Queer Theory and Gender Studies, whether textbooks launch critical perspectives in drama contents and activities for issues of race, gender, sexuality and social class. The objective of the analysis is to assist in the preparation of future textbooks, as well as to contribute to the training of teachers in Theater degree courses. It was concluded that from the listed categories that drama teaching is merely illustrative in textbooks.